2010
DOI: 10.3171/2010.9.focus10201
|View full text |Cite
|
Sign up to set email alerts
|

Cranial bone defects: current and future strategies

Abstract: Bony defects in the craniomaxillofacial skeleton remain a major and challenging health concern. Surgeons have been trying for centuries to restore functionality and aesthetic appearance using autografts, allografts, and even xenografts without entirely satisfactory results. As a result, physicians, scientists, and engineers have been trying for the past few decades to develop new techniques to improve bone growth and bone healing. In this review, the authors summarize the advantages and limitations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
123
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(127 citation statements)
references
References 127 publications
(118 reference statements)
0
123
0
4
Order By: Relevance
“…Repair of cranio-maxillofacial deformation or calvarial bone defects caused by hereditary diseases, severe trauma, resection, or tumors still has limitations. 1 Numerous studies on various biomaterials and cellbased therapies have sought to regenerate bone tissue. Many types of bioceramics and growth factors have been used with biodegradable polymer scaffolds for osteogenesis of mesenchymal stem cells (MSCs) or preosteoblasts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Repair of cranio-maxillofacial deformation or calvarial bone defects caused by hereditary diseases, severe trauma, resection, or tumors still has limitations. 1 Numerous studies on various biomaterials and cellbased therapies have sought to regenerate bone tissue. Many types of bioceramics and growth factors have been used with biodegradable polymer scaffolds for osteogenesis of mesenchymal stem cells (MSCs) or preosteoblasts.…”
mentioning
confidence: 99%
“…Many types of bioceramics and growth factors have been used with biodegradable polymer scaffolds for osteogenesis of mesenchymal stem cells (MSCs) or preosteoblasts. 1,2 Coating or mixing of hydroxyapatite or b-TCP with bone substitutes enhances bone regeneration due to their osteoconductivity and osteoinductivity. 3 It has also been reported that MSCs derived from bone marrow or adipose tissue can improve regeneration efficiency.…”
mentioning
confidence: 99%
“…Defek tulang kepala (cranial bone defects) dan defek tulang wajah (cranio facial defects) merupakan kasus medis dimana tidak adanya jaringan tulang pada bagian cranial dan facial [1] [2], [3], [4]. Defek tersebut dapat menyebabkan berkurangnya fungsionalitas tulang kranial dan perubahan anatomi [4].…”
Section: A Latar Belakangunclassified
“…Defek tersebut dapat menyebabkan berkurangnya fungsionalitas tulang kranial dan perubahan anatomi [4]. Rekonstruksi dan redesain/perbaikan pada defek tulang kepala disebut sebagai tindakan cranioplasty [5].…”
Section: A Latar Belakangunclassified
“…The first studies using fiber-reinforced composites (FRCs) in medicine and dentistry occurred in the early 1960s, but more extensive research started in the early 1990s which led to introduction of FRCs as reconstructive material for damaged dental hard tissues [14][15][16][17][18]. The first approved surgical applications were found in cranial surgery [18].…”
Section: Introductionmentioning
confidence: 99%